Broadband communications and home networking - Bullock, Scott R. 1950- (Noble Publishing Corporation, 2001)
The speed of change in digital communications is most prominently represented by broadband communication and home networking technologies. This easy-to-read book takes a close look at current high-speed digital communications, data distribution and networking solutions for homes and small offices. The comprehensive review of the basic principles and terminology surrounding telephony, modems, digital modulation and orthogonal signals provides a solid background for more advanced discussions.